Awareness of colorectal cancer and barrier of its screening among young adults in health campus of Universiti Sains Malaysia - Tin, Ding Hui (Universiti Sains Malaysia, 2024)
Colorectal cancer (CRC) has been one of the leading causes of death worldwide despite being one of the preventable and treatable cancers upon early diagnosis. The increase in the incidence of CRC has led to numerous studies being conducted to study the knowledge, awareness and barrier to screening regarding CRC globally. Most of the studies done in Malaysia studies the knowledge and awareness of risk factors and warning signs of CRC, however there are no study that investigates the awareness of CRC and potential barrier to its screening have been done among university students. Thus, cross-sectional studies have been carried out from January 2024 till August 2024 to determine the level of awareness of colorectal cancer and the barrier of its screening among young adults in Health Campus of Universiti Sains Malaysia. 228 students of Health Campus of Universiti Sains Malaysia participated in this study by answering the questionnaire through the link of Google Form that is sent via email. The data collected was analysed through SPSS version 27.0. Sociodemographic factors, level of awareness of CRC and potential barrier in getting CRC screening were presented in descriptive statistics. Besides, the association between sociodemographic factor and awareness of CRC was analysed by Pearson’s Chi Square. Unexpectedly, most of the student of Universiti Sains Malaysia have fair knowledge of CRC. There are significant association between year of study and course of study with awareness of CRC. However, there is no significant association between age, gender, ethnicity, family’s monthly income, family history with